Pengaruh Pemahaman Peraturan Perpajakan Terhadap Kepatuhan Wajib Pajak Dengan Preferensi Risiko Sebagai Variabel Moderasi - Bima Perdana Putra; Henri Agustin; Mia Angelina Setiawan (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to see the effect of tax knowledge to taxpayer compliance with risk preference as a moderating variable. The sample in this study are taxpayer in the city of Padang as much as 156 sample. The analysis was done by using moderating regression model analysis. The results of this study indicate that: (1) tax knowledge has positive effect on the taxpayer compliance. (2) risk preference are able to moderate the relationship between tax knowledge to tax compliance